Family Support for Anxiety Facing Menarche in School-Age Children - Pawestri Pawestri; Sri Rejeki; Maudy Yolanda (Media Keperawatan Indonesia, 2023)
The first menstruation (menarche) in early adolescents causes anxiety. Family support is needed in dealing with adolescent anxiety so that young women are ready to face menarches such as knowledge, age, self-perception, and attitudes. The research design is quantitative and descriptive using a correlational approach. This research was conducted in July - August 2022. The number of samples in this research was 50 people. Based on a family support survey conducted by SMP Negeri 29 Semarang for grade 7 students, 27 (54.0%) and 28 (56.0%) respondents had anxiety about family support. Based on the Spearman Rank test results, it has a p = 0.013, p a (0.013 0.05). The calculated coefficient value is 0.350 (35.0%), indicating a negative relationship. The degree of increase in the number of respondents increased directly proportional to the ratio of family support. Most respondents have moderate family support, namely 27 respondents (54.0%). The school hopes that the research findings will be able to become reproductive health learning materials or materials, given the importance of education related to reproductive health.